Desain Kemasan Sambal yang Ergonomis dan Menarik bagi Generasi Milineal dan Generasi Z - Hidayah, Muhammad Nur Wahyu; Wibowo, Eko Ari; Munandar, Galih Mahardika; Betanursanti, Ida; Jauhari, Kun Ihza (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Sambal is one of the favorite foods as an accompaniment to meals for Indonesian people, not only parents but the millennial generation and Generation Z also like chili food. The aim of this research is to design ergonomic chili packaging for the millennial generation and Generation Z. The method used in this research uses the Quality Function Deployment (QFD) method by considering consumer aspects. The research results show that the first priority for improvement is redesigning the label on the product. The second priority is providing a seal (aluminum foil) on the packaging to ensure the hygiene and durability of the chili sauce. The third priority is that the chili bottle uses a thicker plastic material to make it sturdy. The fourth priority is changing the chili brand design by adding a chili logo to make it more attractive and bold in describing the product. The fifth priority is to make the chili packaging bottles more oval so that the shape is more ergonomic and easier to hold. The sixth priority is to add a small spoon to every product purchased because usually this packaged chili sauce is used for food outside the home. The seventh priority is increasing the capacity of chili sauce, which previously weighed 100 grams to 150 grams. Keywords: Generation Z, Millennial Generation, QFD, Sambal Packaging